Analisis Keberlanjutan Dan Strategi Pengembangan Wisata Desa â€œEmbung Pedangâ€ Di Desa Kepohkidul - Novi Nostalgianti; Moh Khusaini; Rita Parmawati (Postgraduate, University of Mataram, 2024)
Tourism development in East Java is considered appropriate because it will have an impact on the economic activities of village communities. Kepohkidul Village, Kedungadem District, Bojonegoro Regency has a tourist attraction, namely